Quality improvement in the implementation science paradigm in professional programs: scoping review. - de Aquino Lemos Corrêa, Bruna Luísa Melo; Ferreira Santana, Rosimere; da Silva Rocha, Greiciane; Marques Bandeira, Tatiany; Gomes do Carmo, Thalita; Siqueira de Carvalho, Ana Carolina (Revista Gaucha de Enfermagem, 2023)
Objective: To map knowledge regarding Quality Improvement in the implementation science paradigm in graduate nursing education in professional programs. Method: This is a scoping review, conducted from October to December 2021, following the assumptions established by the Joanna Briggs Institute and the PRISMA-ScR protocol. Results: 18 studies were selected. Being, 7 articles (38.8%) about the implementation strategies and development of Quality Improvement projects for graduate nursing students. The included studies emphasize Quality Improvement as a methodological strategy capable of capturing a problem in practice, to be solved without losing scientific rigor, and emphasize the importance of obtaining Quality Improvement skills in professional programs. Conclusion: Implementation science and Quality Improvement projects advance professional programs to improve and develop quality health care.